Oil palm waste to green energy : Co-torrefied oil palm pellet (Co-TOPP) - Chang, Siaw Sang; Suriyati, Saleh; Noor Asma Fazli, Abdul Samad (2021)
Combination of torrefaction and copelletization process on producing high quality biofuel pellets form oil palm solid waste. Blending different type of oilpalm solid waste to produce environmentally friendly pellets.